PENGARUH MEDIA GAMBAR BERBASIS NILAI-NILAI ISLAMI TERHADAP KECERDASAN KOGNITIF ANAK (STUDI KASUS: KELAS II SDN 008 KUALU) - Wahyudi Saputra; Risnawati, Risnawati; Fikri Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the results of field observations on the face of cognitive intelligence in children who have not yet developed, it is better to use image media based on Islamic values. The purpose of this research is to find out the influence of Islamic values-based image media on the cognitive intelligence of grade II students of SDN 008 Kualu. The subject of the current research is the influence of image media on children's cognitive intelligence based on Islamic values. The population in this study is as many as 20 children, while the sample for the current study is class II children who are divided into two groups.mNamely, Group 1 with 10 children as the control class and Group 2 with 10 children in the experimental class. Sampling techniques are carried out using sampling techniques.That is, sampling techniques are taken into consideration with certain considerations.iData acquisition techniques used in research are i.e. observation, and documentation. In the data analysis method, the researcher uses the SPSSiWindowsiver program.17. The hypothesis in the study is that there is a significant influence between the media and the image on children's cognitive intelligence based on Islamic values. This can be seen from the results of data analysis that compares the pre-test and post-test of the experimental class. As a result, tcal = 46.819 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 < 0.05, the conclusion is that there is a significant influence after the use of Islamic values-based image media in learning.kArtinyanHonrejectidaniHai accepted, where this researcher has an influence of Islamic values-based image media before and after on the cognitive intelligence of children in the experimental class. The influence of image media of Islamic values of SDN 008 Kualu Class II children on cognitive intelligence was 88.78%.